DETERMINAN PERTUMBUHAN BALITA USIA 6-59 BULAN DI KOTA KENDARI - Bungawati Bungawati; Devi Safitri Effendy; Adius Kusnan (NHM PRESS, 2023)
Growth is one indicator which states that good nutrition is when the nutrition is sufficient and given from an early age. Growth problems. Fulfillment of nutrition that has not been fulfilled properly from in the womb until the baby is born can cause various health problems that affect the growth and development of children. The impact due to the lack of fulfillment of children's needs during the golden age period includes cognitive impairment, stunting or short stature, as well as speech delays and behavioral disorders. The research was conducted to determine the influence of the monitoring program on toddler development in Kendari City. The research was conducted at Benu-Benua Health Center, West Kendari District and Nambo Health Center, Nambo District, Kendari City, Southeast Sulawesi. The time of this research was carried out in January 2023 until it was completed. The type of research used is analytic observational research, with the research design used is cross sectional. The sample in this study amounted to 120 people. The data analysis technique used is multiple linear regression analysis. The results of the research show that partially knowledge has a significant effect on infant growth, perception has a significant effect on infant growth. Family support has a significant effect on infant growth